Handbook of Multiple Sclerosis - Cohen, Jeffrey A.; Rae-Grant, Alexander; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2012)
Over the past 30 years there have been significant advances in our understanding of multiple sclerosis (MS) due to the use of MRIs to better visualize the disease and because of the introduction of new ameliorating drugs. However, MS is still an incurable disease and diagnosis remains challenging for many physicians; for instance symptoms often mimic MS and there is not a specific test for the disease. To ensure optimal patient care there is a need for physicians to remain up to date with new drugs on the market, disease detection, diagnosis, and latest management options. The Handbook of Multiple Sclerosis (Second Edition) provides a concise, easily assessable guide for all healthcare professionals involved in the diagnosis and management of this condition, including standard therapies, as well as more novel treatments. The book includes comprehensive evaluations of the pharmacological treatments available, including novel investigational agents currently in development.
Introduction -- Clinical features -- Diagnosing multiple sclerosis -- Treatment of acute relapses of multiple sclerosis -- Disease modifying therapy -- Symptom management -- Medical management of patients with multiple sclerosis.
Keywords: Medicine; Family medicine; Radiology, Medical; Neurology; Emergency medicine; Medicine & Public Health; Neurology; Neuroradiology; Imaging / Radiology; General Practice / Family Medicine; Primary Care Medicine